Of Natural Risks and Social Catastrophes – The Didactical Reconceptualization of a Traditional Topic in Geography Teaching - Otto, Karl-Heinz (Journal of Geography Education, 2009)
Natural disasters is one of the oldest topics in geography teaching in German secondary schools, especially in grades 7 or 8. In teaching practice, the actual, short term catastrophic events usually take centre stage, while both processes as well as the social aspects of natural disasters tend to be neglected. Recent research on hazards and risks suggest a somewhat different treatment of these topics in geography teaching, focussing primarily on the ideas of natural risks and social catastrophes.